Polyoxymethylene dimethyl ether 3 (PODE3) as an alternative fuel to reduce aerosol pollution. (20th February 2021) - Lin, Qinjie; Tay, Kun Lin; Yu, Wenbin; Zong, Yichen; Yang, Wenming; Rivellini, Laura-Hélèna; Ma, Mutian; Lee, Alex King Yin
Abstract: Polyoxymethylene dimethyl ether 3 (PODE3 ) is a highly promising renewable fuel. Not only does it have physical characteristics which are suitable for practical engine applications, but it is also expected to facilitate prominent soot reduction. In this work, neat PODE3 is added to diesel in an engine to evaluate its practicality in terms of curbing aerosol pollution arising from diesel engines, as well as improving energy efficiency for easing global energy shortage. PODE3 has been found capable of offering soot reduction across all engine loads. In particular, 20% of PODE3 addition to diesel has demonstrated soot reduction at all loads, with a remarkable particulate matter reduction factor of 3.55 at 50% load. However, although with such impressive 71.8% soot reduction at medium load, it can cause a spike increase of 71.2% in particle number concentration, owing largely to ultrafine particles. Furthermore, it has been discovered that PODE3 contributes minimal changes to energy efficiency and that the usage of PODE3 has minimal impact on the fuel economy by virtue of PODE3 's high density. Moreover, a manifestation of a nucleation-accumulation mode particle trade-off relationship has been observed in this work. The evaluation of PODE3 's practicality serves to bring into perspective the practicality of the fuel in terms of realistic utilization, to set it in a critical context for providing insights towards future research. Highlights: Investigation of PODE3 has been conducted in a diesel engine. P20 shows soot reduction at all loads, with up to 71.8% reduction at medium load. Particle number concentration decreases at low and high loads with usage of P20. Geometric mean diameter of particles decreases with PODE3 addition. PODE3 performs well only in certain ranges of engine operating conditions.